What is "evidence-based" strength and conditioning? - English, K. L.; Amonette, W. E.; Graham, M.; Spiering, B. A. (Strength and Conditioning Journal, 2012)
The term "evidence-based" has begun appearing in the field of strength and conditioning. However, this term has yet to be formally introduced to the strength and conditioning community. Far from being a mere buzzword, evidence-based practice (EBP) is a defined process by which practitioners (in this instance, strength and conditioning professionals) incorporate the "best" available evidence into the everyday training of athletes and clients. Incorporation of EBP into the strength and conditioning field will improve the quality of training programs provided for athletes and clients and increase the prestige and standing of our discipline.